Screening for chronic comorbid diseases in people with HIV: the need for a strategic approach. (2nd November 2012) - Peters, B; Post, F; Wierzbicki, AS; Phillips, A; Power, L; Das, S; Johnson, M; Moyle, G; Hughes, L; Wilkins, E; McCloskey, E; Compston, J; et al.
Abstract : Among people living with HIV, the proportion of deaths attributed to chronic noninfectious comorbid diseases has increased over the past 15 years. This is partly a result of increased longevity in the era of highly active antiretroviral therapy (HAART), and also because HIV infection is related, causally or otherwise, to several chronic conditions. These comorbidities include conditions that are strongly associated with modifiable risk factors, such as cardiovascular disease (CVD), diabetes, and renal and bone diseases, and increasingly management guidelines for HIV recommend risk evaluation for these conditions. The uptake of these screening approaches is often limited by the resources required for their application, and hence the management of risk reduction in most HIV‐infected populations falls below a reasonable standard. The situation is compounded by the fact that few risk calculators have been adjusted for specific use in HIV infection. There is substantial overlap of risk factors for the four common comorbid diseases listed above that are especially relevant in HIV infection, and this offers an opportunity to develop a simple screening approach that encompasses the key risk factors for lifestyle‐related chronic disease in people with HIV infection. This would identify those patients who require more in‐depth investigation, and facilitate a stepwise approach to targeted management. Such a tool could improve communication between patient and clinician. A significant proportion of people with HIV are sufficiently engaged with their care to participate in health promotion and take the lead in using patient‐centric screening measures. Health‐based social networking offers a mechanism for dissemination of such a tool and is able to embed educational messages and support within the process.